Suggestions and debates : the national integration of European working classes (1871-1914) : exploring the causal configuration - van der Linden, Marcel ([Cambridge]: [University Press], 1988)
"Marcel van der Linden Bibliotheek François VercammenOverdruk van International Review of Social History, vol. 33 (1988), nr. 3"